Bacteroidaceae, Bacteroides, and Veillonella: emerging protectors against Graves’ disease - Liu, Siyuan; Li, Fan; Cai, Yunjia; Ren, Linan; Sun, Lin; Gang, Xiaokun; Wang, Guixia (Frontiers in Cellular and Infection Microbiology, 2024)
Background Graves’ disease (GD) is the most common cause of hyperthyroidism, and its pathogenesis remains incompletely elucidated. Numerous studies have implicated the gut microbiota in the development of thyroid disorders. This study employs Mendelian randomization analysis to investigate the characteristics of gut microbiota in GD patients, aiming to offer novel insights into the etiology and treatment of Graves’ disease. Methods Two-sample Mendelian randomization (MR) analysis was employed to assess the causal relationship between Graves’ disease and the gut microbiota composition. Gut microbiota data were sourced from the international consortium MiBioGen, while Graves’ disease data were obtained from FINNGEN. Eligible single nucleotide polymorphisms (SNPs) were selected as instrumental variables. Multiple analysis methods, including inverse variance-weighted (IVW), MR-Egger regression, weighted median, weighted mode, and MR-RAPS, were utilized. Sensitivity analyses were conducted employing MR-Egger intercept test, Cochran’s Q test, and leave-one-out analysis as quality control measures. Results The Mendelian randomization study conducted in a European population revealed a decreased risk of Graves’ disease associated with Bacteroidaceae (Odds ratio (OR) [95% confidence interval (CI)]: 0.89 [0.89 0.90], adjusted P value: <0.001), Bacteroides (OR: [95% CI]: 0.555 [0.437 0.706], adjusted P value: <0.001), and Veillonella (OR [95% CI]: 0.632 [0.492 0.811], adjusted P value: 0.016). No significant evidence of heterogeneity, or horizontal pleiotropy was detected. Furthermore, the preliminary MR analysis identified 13 bacterial species including Eubacterium brachy group and Family XIII AD3011 group, exhibiting significant associations with Graves’ disease onset, suggesting potential causal effects. Conclusion A causal relationship exists between gut microbiota and Graves’ disease. Bacteroidaceae, Bacteroides, and Veillonella emerge as protective factors against Graves’ disease development. Prospective probiotic supplementation may offer a novel avenue for adjunctive treatment in the management of Graves’ disease in the future.